The Close Association Of E Faecalis And NLRP3 Inflammasome In Pulpal Diseases. (International Journal of Food and Nutritional Sciences, 2022)
Since Enterococcus Faecalis is the most frequently found microbial pathogen in root canals with persistent infection, its discovery seriously impairs any case's prognosis. 1,2 This species' capacity to infiltrate dentinal tubules and withstand intracanal medications is largely responsible for its survival.3,4 A recent study has established the link between E. faecalis and extra-radicular infection in addition to intra-radicular infection.3However, according to other findings, E faecalis is not the most common species and is not found in apical biofilms in patients with post-treatment apical periodontitis.3,4 The aforementioned findings further demonstrate that it is unclear how E faecalis contributes to endodontic disorders. Therefore, it is necessary to improve knowledge, but in order to do so, it is important to discuss a clear molecular picture.